Quantitative evaluation of bone scintigraphy of the spinous processes of the equine thoracic spine at different times after administering 99m Tc‐hydroxymethylene‐diphosphonate. (17th May 2014) - Sporn, A.; Berner, D.; Winter, K.; Mageed, M.; Brehm, W.; Gerlach, K.
Abstract : Scintigraphic examination of the thoracic spine is well documented. However, there is limited information about the effects of time on image quality in the period following injection of radionuclide. This study aimed to determine the optimal time point after injection of 99m Tc‐HDP (hydroxymethylene‐diphosphonate) to achieve scintigraphic images with the best possible contrast and adequate count rates. Scintigraphic images of the thoracic spine of 21 horses were acquired two, four and six hours after administering 99m Tc‐HDP. Eight regions of interest were drawn in the images, four in the spinous processes and four in the adjacent soft tissue. The bone uptake, soft tissue uptake and the bone‐to‐soft tissue ratio were determined and compared between the different time points. Total count rates decreased with time after injection, but were at least as high as 150, 000 counts per image at every time point after injection. The bone‐to‐soft tissue ratio was significantly higher for the images acquired after six hours compared to those acquired after two and four hours (P<0.01). Delayed scintigraphic examinations of the spinous processes of the equine thoracic spine achieved images with high contrast and sufficient count rates. Therefore, the scintigraphic examination of the equine thoracic spine is recommended to be done four to six hours after injecting 99m Tc‐HDP. However, additional studies should be performed to determine the effect of delayed image acquisition compared to images taken after three hours on the detectability of lesions in other parts of the thoracic spine and the soft tissue.